Analisis Wacana Kritis Berita Kekerasan di Pesantren Pada Media Sosial - Nadzifah, Ainun; Refti Handini Listyani (Paradigma, 2025)
Abstract The news of the case of a Gontor student allegedly abused by a senior in 2022 has become a new bullying issue among teenagers. News in the media says that Islamic boarding schools are a safe place for children's education, which has become a false stigma and various other opinions. This research is interesting to do because the stigma and opinion appear depending on the use of words and sentences from the media in its reporting. This research is descriptive qualitative and aims to explain the phenomenon in depth related to the news of the Gontor Islamic boarding school on several social media. The analysis technique used is Vandijk's critical discourse analysis method by looking at 3 dimensions, text analysis, social cognition and social context. The results and discussion in this study are the discourse of the Islamic boarding school which has become bad due to the victim's mother Soimah expressing her feelings, what she heard and what she saw. The discourse of the Islamic boarding school on irresponsible attitudes, not being open and other dark side assumptions. Some content on social media is a form of support for the victim's mother because of the injustice and disappointment she felt so that the media succeeded in creating a stigma in society. The legal counsel acts as a pro party to the family, appearing in the media to help Soimah who is unable to accept this incident. Gontor is considered to have disappointed and lied trying to give an explanation and apologize to the media. The context of most people considers that Gontor as a famous Islamic boarding school uses their power in education because the Islamic boarding school system led by kyai has a patron-client role of society. Keywords: Critical Discourses Analysis, Social media, islamic boarding school power relations Pemberitaan kasus santri gontor diduga dianiaya senior pada tahun 2022 menjadi isu bullying baru di kalangan remaja. Berita di media mengatakan bahwa pondok pesantren merupakan tempat cukup aman untuk pendidikan anak menjadi stigma yang salah dan berbagai opini yang lain. Penelitian ini menarik dilakukan karena stigma dan opini tersebut muncul bergantung pada penggunaan kata dan kalimat dari media pada pemberitaannya. Penelitian ini bersifat deksriptif kualitatif bertujuan menjelaskan fenomena secara mendalam terkait pemberitaan pesantren Gontor di beberapa media sosial. Teknik analisis yang digunakan yaitu metode analisis wacana kritis milik vandijk dengan melihat 3 dimensi, analisis teks, kognisi sosial dan konteks sosial. Hasil dan pembahasan pada penelitian ini yaitu wacana pesantren yang menjadi jelek akibat dari ibu korban Soimah mengungkapkan perasaannya, apa yang dia dengar dan apa yang dia lihat. Wacana pesantren atas sikap yang tidak bertanggungjawab, tidak terbuka dan anggapan sisi gelap lainnya. Beberapa konten pada media sosial merupakan bentuk dukungan kepada ibu korban karena ketidakadilan dan kecewa yang dia rasakan sehingga media berhasil membuat suatu stigma di masyarakat. Kuasa hukum berperan sebagai pihak pro kepada keluarga banyak tampil di media untuk membantu Soimah yang tidak mampu menerima kejadian ini. Pihak gontor dianggap membuat kecewa dan berbohong mencoba memberi penjelasan dan meminta maaf kepada media. Konteks sebagian besar masyarakat menganggap bahwa Gontor sebagai pesantren ternama memanfaatkan kuasa mereka dalam pendidikan karena sistem pesantren yang dipimpin oleh kyai mempunyai peran patron-client of society. Kata Kunci: Analisis Wacana kritis, Media Sosial, Islamic Boarding school power relations